Pengujian Karakteristik Alat Ukur Radiasi Dose Calibrator Menggunakan Sumber Teknesium-99m di Instalasi Kedokteran Nuklir Rumah Sakit Abdoel Wahab Sjahranie Samarinda - Mutmainna, Fahira Mutya; Wardani, Pratiwi Sri; Putri, Erlinda Ratnasari; Zurma, Retno (Progressive Physics Journal, 2024)
Dose Calibrator is one of the dosimeters used to measure radionuclide activity before being given to patients. In order to function as a radiation dosimeter, the dose calibrator must have several good dosimeter properties such as precision and stability. To test the dose calibrator, a source used by the hospital is required. One isotope that is widely used in the field of nuclear medicine, namely Tc-99m. The research steps this time are: firstly the elution performed by radiopharmaceuticals, secondly measuring background activity (background), thirdly calling for Tc-99m sources, fourthly measuring Tc-99m activity, fifthly calculating Tc-99m activity for testing precision, and sixth evaluate the results. Based on the research results on the precision test, it was found that the measurement results for the Tc-99m source were obtained at 0.578%. It can be concluded that the Capintec CRC 25R dose calibrator has good characteristics and performance, so that the measurement results can be trusted.